Prevalence and prognostic impact of cognitive frailty in elderly patients with heart failure: sub‐analysis of FRAGILE‐HF - Shuhei Yamamoto; Saeko Yamasaki; Satoko Higuchi; Kentaro Kamiya; Hiroshi Saito; Kazuya Saito; Yuki Ogasahara; Emi Maekawa; Masaaki Konishi; Takeshi Kitai; Kentaro Iwata; Kentaro Jujo; et al. (ESC Heart Failure)
Abstract Aims Although evidence suggests that cognitive decline and physical frailty in elderly patients with heart failure (HF) are associated with prognosis, the impact of concurrent physical frailty and cognitive impairment, that is, cognitive frailty, on prognosis has yet to be fully investigated. The current study sought to investigate the prevalence and prognostic impact of cognitive frailty in elderly patients with HF. Methods and results This study is a sub‐analysis of FRAGILE‐HF, a prospective multicentre observational study involving patients aged ≥65 years hospitalized for HF. The Fried criteria and Mini‐Cog were used to diagnose physical frailty and cognitive impairment, respectively. The association between cognitive frailty and the combined endpoint of mortality and HF rehospitalization within 1 year was then evaluated. Among the 1332 patients identified, 1215 who could be assessed using Mini‐Cog and the Fried criteria were included in this study. Among those included, 279 patients (23.0%) had cognitive frailty. During the follow‐up 1 year after discharge, 398 combined events were observed. Moreover, cognitive frailty was determined to be associated with a higher incidence of combined events (log‐rank: P = 0.0146). This association was retained even after adjusting for other prognostic factors (hazard ratio: 1.55, 95% confidence interval: 1.13–2.13). Furthermore, a sensitivity analysis using grip strength, short physical performance battery, and gait speed to determine physical frailty instead of the Fried criteria showed similar results. Conclusions This cohort study found that 23% of elderly patients with HF had cognitive frailty, which was associated with a 1.55‐fold greater risk for combined events within 1 year compared with patients without cognitive frailty.